2015
DOI: 10.3389/fnagi.2014.00340
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of nicotine, cotinine and its metabolites as potential agents for Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder, which is characterized by neuroinflammation, dopaminergic neuronal cell death and motor dysfunction, and for which there are no proven effective treatments. The negative correlation between tobacco consumption and PD suggests that tobacco-derived compounds can be beneficial against PD. Nicotine, the more studied alkaloid derived from tobacco, is considered to be responsible for the beneficial behavioral and neurological effects of tobacco us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 153 publications
1
73
0
3
Order By: Relevance
“…It is possible that nicotine exposure in the farmworkers may be related to reductions in brain iron deposition in the putamen and cerebellum. This is consistent with the data indicating that nicotine is protective against PD [2127], and that PD patients have increased brain iron accumulation [7375]. Multiple mechanisms have been proposed for antioxidant effects of nicotine including reduced glutamate release [76], direct binding of iron [77, 78], as well as nicotine-induced increases in ascorbate in the basal ganglia and nucleus accumbens [79].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is possible that nicotine exposure in the farmworkers may be related to reductions in brain iron deposition in the putamen and cerebellum. This is consistent with the data indicating that nicotine is protective against PD [2127], and that PD patients have increased brain iron accumulation [7375]. Multiple mechanisms have been proposed for antioxidant effects of nicotine including reduced glutamate release [76], direct binding of iron [77, 78], as well as nicotine-induced increases in ascorbate in the basal ganglia and nucleus accumbens [79].…”
Section: Discussionsupporting
confidence: 87%
“…Acute exposure to nicotine through a medication or cigarette smoking is known to enhance attention and concentration [1820]. Long-term smoking has been shown to be protective against Parkinson’s disease (PD), a disease known to be associated with reduced brain dopamine [2127]. The mechanism underlying this protective effect remains unknown but may be related to nicotine-induced dopamine release [28] or to reduced oxidative stress when nicotine binds free iron [29].…”
Section: Introductionmentioning
confidence: 99%
“…First, the database used in our study did not contain clinical laboratory test values, namely the LDL cholesterol levels, which were shown to be inversely associated with PD . Second, various factors such as the nutrition status (vitamin C intake), nicotine levels, alcohol consumption, and smoking status could affect PD incidence or progression, but these data were not available in our study. However, these confounding factors cannot fully explain the protective effects of statin, because these factors are not related to statin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is still considered a toxic and addictive compound, but it has been shown that it is also a positive cholinergic modulator showing pro‐cognitive, anti‐inflammatory, neuroprotective and antioxidant properties (Barreto, Iarkov, & Moran, ). Interestingly, our results showed significant differences in the viability of A549 cells between PG and PG + nicotine solutions, at a concentration range from 0.125% to 1%, which may be a result of the cytoprotective effect of nicotine.…”
Section: Discussionmentioning
confidence: 99%